Pengaruh Kompetensi Auditor, Kompleksitas Tugas, Skeptisme Professional terhadap Kualitas Audit dengan Due Professional Care sebagai Variabel Moderating pada Kantor Akuntan Publik di Medan - Tanady, Sophia; Meilavia, Jessy; Sitepu, Wilsa Road Betterment (JURNAL MUTIARA AKUNTANSI, 2021)
In this modern era, the services of an auditor are very much needed by government agencies and private agencies because the results of the decisions made by auditors can reflect the transparency of an organization. An auditor must have an attitude of competence and good skepticism so that when assessing an organization, no mistakes occur. The attitude of complexity is also an attitude that must be possessed by an auditor where an auditor must be able to know what difficulties or obstacles will be faced in determining the outcome of the decision. Complexity also requires auditors to think about whether the task being carried out can be completed properly or not. The characteristics that exist in the auditor may reflect the quality of the audit produced by the auditor. The research method used is quantitative research methods with all members of public accountants used as population data and the use of the Likert scale as a reference in collecting questionnaire data. From the results of research that has been conducted in Medan, it can be concluded that.